Quantitative measurement of horizontal strabismus with digital photography - ÇERMAN, EREN; DERİCİOĞLU, VOLKAN (MOSBY-ELSEVIER, 2019)
PURPOSE To develop a method to calculate the gaze angle in photographs and to determine its validity and reliability in real strabismus patients. METHODS Photographs of eyes from 15 orthophoric subjects (n = 1,022) with known gaze angle and imaging distance were investigated with the help of a smartphone application developed by the authors. The application provided measurements of the distance from the geometrical center of the cornea to the light reflex (RD) and corneal diameter (CD). The RD/CD ratio of each gaze angle was recorded. To estimate the eyes' gaze angle, an equation to determine the best-fit line for the gaze angle data according to each RD/CD ratio was created. In a second clinical analysis, this equation was applied to photographs of real strabismus patients (n = 72), and the results were compared with measurements taken by a double-masked strabismus specialist. Separately, an equation was created to calculate the imaging distance using the given interpupillary distance. RESULTS There was a high correlation between the real and estimated gaze angles (r = 0.990, P < 0.001). The mean error of the estimated gaze angle was found to be 0.03(Delta) +/- 4.60(Delta). There was a high correlation between the real and estimated imaging distance (r = 0.997, P < 0.001) and a high correlation between the measurements of the application and the specialist (r = 0.966, P < 0.001). The average error was -0.68(Delta) +/- 6.1(Delta), and the reliability was high (Cronbach's alpha = 0.983). CONCLUSIONS The application measured horizontal strabismus in photographs with high reliability.